2014
DOI: 10.1002/cbic.201402195
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Reconstitution of Biosynthetic Machinery for Fungal Metabolites in Aspergillus oryzae: Total Biosynthesis of Aflatrem

Abstract: Reconstitution of the biosynthetic machinery for fungal secondary metabolites in Aspergillus oryzae provides an opportunity both for stepwise determination of the biosynthetic pathways and the total biosynthesis of fungal natural products. However, to maximize the utility of the reconstitution system, a simple and rapid strategy for the introduction of heterologous genes into A. oryzae is required. In this study, we demonstrated an effective method for introducing multiple genes involved in the biosynthesis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
69
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 72 publications
(71 citation statements)
references
References 39 publications
2
69
0
Order By: Relevance
“…Representative examples are found in the total biosynthesis of tenellin, 11 aphidicolin, 12 paxilline, 13 aspyridone, 14 aflatrem, 15 and anditomin (11 + 1 genes). 16 For skeletal construction of 1 in A. oryzae, bet1 and bet3 genes were subcloned into fungal expression vectors, pUARA2 (argB marker) and pUSA2 (sC marker), 15 to construct pUARA2-bet1 and pUSA2-bet3, which were then introduced into A. oryzae NSAR1 to construct both a bet1 single transformant and a bet1/3 double transformant ( The 1 H-NMR spectrum of the product completely agreed with that of 4, 9 allowing us to determine the structure of the observed metabolite as 5. These results showed that the collaborative action of Bet1 and Bet3 plays a key role in the skeletal construction of 5 in betaenone biosynthesis.…”
mentioning
confidence: 99%
“…Representative examples are found in the total biosynthesis of tenellin, 11 aphidicolin, 12 paxilline, 13 aspyridone, 14 aflatrem, 15 and anditomin (11 + 1 genes). 16 For skeletal construction of 1 in A. oryzae, bet1 and bet3 genes were subcloned into fungal expression vectors, pUARA2 (argB marker) and pUSA2 (sC marker), 15 to construct pUARA2-bet1 and pUSA2-bet3, which were then introduced into A. oryzae NSAR1 to construct both a bet1 single transformant and a bet1/3 double transformant ( The 1 H-NMR spectrum of the product completely agreed with that of 4, 9 allowing us to determine the structure of the observed metabolite as 5. These results showed that the collaborative action of Bet1 and Bet3 plays a key role in the skeletal construction of 5 in betaenone biosynthesis.…”
mentioning
confidence: 99%
“…GGI is then converted to an epoxide by the action of an epoxidase (PaxM/AtmM) and subsequently transformed by an IDT cyclase (PaxB/AtmB) to the first stable intermediate, paspaline 150,151) . In A. flavus, paspaline is then converted to paspalinine by the action of the cytochrome P450 monooxygenases AtmP and AtmQ followed by subsequent conversion to aflatrem by the prenyltransferase AtmD.…”
Section: -5 Aflatrem Clustersmentioning
confidence: 99%
“…Ultimately, a yield of 35 mg L −1 of the final product was reported in A. oryzae . Adopting a similar approach, the same research group also recreated biosynthesis of aflatrems (22), indole-diterpene compounds with similar structure and properties to those of paxilline (Tagami et al 2014). Insertion of the first four genes of the pathway from the original host A. flavus into A. oryzae allowed them to achieve production of paspaline, a common precursor to aflatrems, paxilline, and other indole-diterpenes.…”
Section: Heterologous Expression In Filamentous Fungimentioning
confidence: 99%
“… a The yield in the heterologous host is expressed as mg of compound produced per litre of liquid medium b The yield, in this case, is expressed as mg of compound per Kg of rice, as the heterologous host was grown in a solid medium made of polished rice (100 g) and adenine (10 mg) (Tagami et al 2014)…”
Section: Heterologous Expression In Filamentous Fungimentioning
confidence: 99%
See 1 more Smart Citation